Clinical effects and pharmacokinetics of nebulized lidocaine in healthy horses - Minuto, Jillian; Bedenice, Daniela; Ceresia, Michelle; Zaghloul, Iman; Böhlke, Mark; Mazan, Melissa R. (Frontiers in Veterinary Science, 2022)
Background: Nebulized lidocaine appears promising as a novel corticosteroid-sparing therapeutic for equine asthma, but its safety and pharmacokinetic behavior have yet to be confirmed. Objective: To describe the effect of nebulized lidocaine on upper airway sensitivity, lung mechanics, and lower respiratory cellular response of healthy horses, as well as delivery of lidocaine to lower airways, and its subsequent absorption, clearance, and duration of detectability. Animals: Six healthy university- and client-owned horses with normal physical examination and serum amyloid A, and no history of respiratory disease within 6 months. Methods: Prospective, descriptive study evaluating the immediate effects of 1 mg/kg 4% preservative-free lidocaine following nebulization with the Flexineb®. Prior to and following nebulization, horses were assessed using upper airway endoscopy, bronchoalveolar lavage, and pulmonary function testing with esophageal balloon/pneumotachography and histamine bronchoprovocation. Additionally, blood and urine were collected at predetermined times following single-dose intravenous and nebulized lidocaine administration for pharmacokinetic analysis. Results: Upper airway sensitivity was unchanged following lidocaine nebulization, and no laryngospasm or excessive salivation was noted. Lidocaine nebulization (1 mg/kg) resulted in a mean epithelial lining fluid concentration of 9.63±5.05 g/mL, and a bioavailability of 29.7±7.76%. Lidocaine concentrations were higher in epithelial lining fluid than in systemic circulation (Cmax 149.23±78.74 g/L, CELF:Cmaxplasma 64.4, range 26.5-136.8). Serum and urine lidocaine levels remained detectable for 24 and 48 hours, respectively, following nebulization of a single dose. Baseline spirometry, lung resistance and dynamic compliance, remained normal following lidocaine nebulization, with resistance decreasing post-nebulization. Compared to the pre-nebulization group, two additional horses were hyperresponsive following lidocaine nebulization. There was a significant increase in mean airway responsiveness post-lidocaine nebulization, based on lung resistance, but not dynamic compliance. One horse had BAL cytology consistent with airway inflammation both before and after lidocaine treatment. Conclusions: Nebulized lidocaine was not associated with adverse effects on upper airway sensitivity or BAL cytology. While baseline lung resistance was unchanged, increased airway reactivity to histamine bronchoprovocation in the absence of clinical signs was seen in some horses following nebulization. Further research is necessary to evaluate drug delivery, adverse events, and efficacy in asthmatic horses.